TORSIONAL BEHAVIOR IN SELF-COMPACTING AND CONVENTIONAL CONCRETE: FINDINGS FROM PAST RESEARCH AND EXPERIMENTS - Kaur, Mandeep; Singh, Dr. Harvinder (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study investigates the torsional behavior of reinforced concrete (RC) beams made with Conventional Concrete (CC) and Self-Compacting Concrete (SCC) under pure torsional loading. The primary variables considered are concrete type, concrete strength class, and web spacing. The torsional moment capacities, crack patterns, and failure mechanisms of the beams were experimentally evaluated and compared to theoretical predictions based on various standards and empirical formulas. The results revealed that SCC beams exhibited significantly improved torsional performance compared to CC beams, due to better adhesion between the cement paste and aggregates, resulting in narrower crack widths and higher torsional moment capacities. Additionally, the study found that decreasing web spacing increased torsional capacity and reduced crack width for both concrete types. The experimental results were compared with theoretical torsional moment values derived from ACI, EU, TS, AS3600, BS8110, Hsu’s, and Rauch’s formulas, with the closest correlation observed with the AS standard. The study highlights the importance of concrete type, concrete strength, and web spacing in enhancing the torsional behavior of reinforced concrete beams and suggests that existing empirical models should be refined to account for the unique characteristics of SCC.